Flamingos use their L-shaped beak and morphing feet to induce vortical traps for prey capture - Victor M. Ortega-Jimenez; Tien Yee; Pankaj Rohilla; Benjamin Seleb; Jake Belair; Saad Bhamla (Proceedings of the National Academy of Sciences, 2025)
Flamingos feature one of the most sophisticated filter-feeding systems among birds, characterized by upside-down feeding, comb-like lamellae, and a piston-like tongue. However, the hydrodynamic functions of their L-shaped chattering beak, S-curved neck, and distinct behaviors such as stomping and feeding against the flow remain a mystery. Combining live flamingo experiments with live brine shrimp and passive particles, bioinspired physical models, and 3D CFD simulations, we show that flamingos generate self-induced vortical traps using their heads, beaks, and feet to capture agile planktonic prey in harsh fluid environments. When retracting their heads rapidly (~40 cm/s), flamingos generate tornado-like vortices that stir up and upwell bottom sediments and live shrimp aided by their L-shaped beak. Remarkably, they also induce directional flows (~7 cm/s) through asymmetric beak chattering underwater (~12 Hz). Their morphing feet create horizontal eddies during stomping, lifting, and concentrating sediments and brine shrimp, while trapping fast-swimming invertebrates, as confirmed by using a 3D-printed morphing foot model. During interfacial skimming, flamingos produce a vortical recirculation zone at the beak’s tip, aiding in prey capture. Experiments using a flamingo-inspired particle collection system indicate that beak chattering improves capture rates by ~7×. These findings offer design principles for bioinspired particle collection systems that may be applied to remove pollutants and harmful microorganisms from water bodies.